Mixed convection heat transfer from a heated circular cylinder - Laidoudi, H; Bouzit, M (Bangladesh Journal of Scientific and Industrial Research, 2019)
This paper performs the effects of thermal buoyancy and the triangular arrangement of circular cylinders on fluid flow and heat transfer within a horizontal channel, the governing equations involving continuity; momentum and energy are solved in two-dimensional, laminar and steady flow regime. The average Nusselt number and drag coefficient are computed for the range of these conditions: Ri = 0 to 2 at fixed value of Pr = 1, Reynolds number Re = 30 and geometrical configurations (blockage ratio of β = 0.1). In order to observe the flow structure and temperature field under the gradual effect of thermal buoyancy, the streamlines and isotherm contours are illustrated. It is found that, a gradual increase in the value of buoyancy strength creates an asymmetrical flow around the cylinders. Interesting variations of drag coefficient and average Nusselt number are plotted with respect to Richardson number for each cylinder. Bangladesh J. Sci. Ind. Res.54(1), 83-88, 2019